Correlation between body composition and leg power of a college cheerleading team - Borillo, Maria Krisanta N. 1996-; Callanta, Hercules (Quezon City College of Human Kinetics, University of the Philippines Diliman, 2019)
Twenty-seven cheerleaders (16 female, 11 male) from a college cheerleading team were measured to determine if there is a correlation between body composition (body fat percentage and muscle mass) and leg power. The height, weight, body fat percentage, muscle mass, and countermovement jump of the participants were assessed. For the countermovement jump, the free software ChronoJump-Boscosystem, chronopic, and a contact mat were used. Three jumps were recorded per participant. The generated peak power that was encoded from the free software was used for the study. The means of the anthropometric measurements and CMJ leg power were calculated. The Pearson Product-Moment Correlation Coefficient was used to determine the correlation between leg power and body composition. Based on the results, male participants had an average body fat percentage and muscle mass of 15.17 += 4.91 and 35.75 +=1.43, respectively; the average of their leg power was 1014.37 += 464.46. For females they had an average body fat percentage and muscle mass of 21.52 += 4.63 and 28.66 += 27.2, respectively; the average leg power for female was 646.72.87. The overall mean of body fat percentage of both genders was 18.94 +=5.64; mean of muscle mass of both gender was 31.55+= 3.93; the mean of leg power for both genders was 705.5+=309.1. There was no significant relationship between body fat percentage and leg power over the whole sample of participants. (rs=0.13, p=0.5031). On the other hand, leg power and skeletal muscle mass were significantly positively correlated (rs=0.53, p=0.0049).
Vita.
Thesis (Bachelor in Sports Science)--University of the Philippines Diliman
Keywords: Leg exercises; Jumping -- Training; Body composition; Cheerleading -- Philippines -- Diliman (Quezon City).